Carbohydrate sulfotransferase 14 gene deletion induces dermatan sulfate deficiency and affects collagen structure and bowel contraction - Fumiko Ono; Yuki Takahashi; Shin Shimada; Shuji Mizumoto; Shinji Miyata; Yuko Nitahara-Kasahara; Shuhei Yamada; Takashi Okada; Tomoki Kosho; Takahiro Yoshizawa (PLoS ONE, 2025)
Dermatan sulfate (DS) is a type of glycosaminoglycan present in the extracellular matrix, and which is related to tissue strength, structure, and healing. Dermatan 4-O-sulfotransferase 1 (D4ST1) is an enzyme that catalyzes the transfer of a sulfate group to the N-acetylgalactosamine residue of dermatan, resulting in mature DS. Biallelic loss-of-function variants in the carbohydrate sulfotransferase 14 (CHST14) gene encoding D4ST1, induce defective DS biosynthesis. DS deficiency causes severe connective tissue fragility and deformities in humans (musculocontractural Ehlers–Danlos Syndrome [mcEDS]) and mice (Chst14 gene knockout [Chst14-/-] mice). Many patients with mcEDS experience gastrointestinal symptoms such as constipation, diverticula, diverticulitis, and perforation. However, pathogenesis of these symptoms has not been systematically investigated. Therefore, we sought to determine the effects of DS deficiency on the colon using Chst14-/- mice. We found that collagen fibrils were abnormally arranged in the submucosa of the colon. The mice also exhibited accelerated colonic contraction. Unexpectedly, no significant aggravation of dextran sulfate sodium-induced colitis was observed in Chst14-/- mice compared with wild-type mice. These findings suggest a physiological role of DS in the colon and may shed light on the potential mechanisms underlying the gastrointestinal symptoms of mcEDS.